Texts from the Swedish Agency for Economic and Regional Growth - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts that have been sent to us direclty by the agency.

Parallella texter som som skickats till oss direkt av Tillväxtverket.
Texter från Tillväxtverket
Keywords: national economy; nationalekonomi; business economics; företagsekonomi; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Social Sciences; Samhällsvetenskap; Economics and Business; Ekonomi och näringsliv; Languages and Literature; Språk och litteratur